Highlights from the ATLAS experiment - Onofre, A. (2019)
This report provides an overview of the new results obtained by the ATLAS Collaboration at the LHC, which were presented at the Quark Matter 2018 conference. These measurements were covered in 12 parallel talks, one flash talk and 11 posters. In this document, a discussion of results is grouped into four areas: electromagnetic interactions, jet quenching, quarkonia and heavy-flavour production, and collectivity in small and larger systems. Measurements from the xenon-xenon collisions based on a short run collected in October 2017 are reported for the first time.